Discovering science electricity book 4 - Barratt, D.H. (Leeds ; E.J. Arnold and Son Ltd, 1962)
Gives instructions for simple experiments that reveal some of the ch aracteristics of electricity.
Includes index.
Keywords: Electricity -- Experiments; Experiments